Risk stratification for selecting empiric antibiotherapy during and after COVID-19. Issue 6 (27th December 2022) - Zahar, Jean-Ralph; Timsit, Jean-Francois
Abstract : Purpose of review: SARS-CoV-2 deeply modified the risk of bacterial infection, bacterial resistance, and antibiotic strategies. This review summarized what we have learned. Recent findings: During the COVID-19 pandemic, we observed an increase in healthcare-acquired infection and multidrug-resistant organism-related infection, triggered by several factors: structural factors, such as increased workload and ongoing outbreaks, underlying illnesses, invasive procedures, and treatment-induced immunosuppression. The two most frequently healthcare-acquired infections described in patients hospitalized with COVID-19 were bloodstream infection, related or not to catheters, health-acquired pneumonia (in ventilated or nonventilated patients). The most frequent species involved in bacteremia were Gram-positive cocci and Gram-negative bacilli in health-acquired pneumonia. The rate of Gram-negative bacilli is particularly high in late-onset ventilator-associated pneumonia, and the specific risk of Pseudomonas aeruginosa- related pneumonia increased when the duration of ventilation was longer than 7 days. A specificity that remains unexplained so far is the increase in enterococci bacteremia. Summary: The choice of empiric antibiotimicrobials depends on several factors such as the site of the infection, time of onset and previous length of stay, previous antibiotic therapy, and known multidrug-resistant organism colonization. Pharmacokinetics of antimicrobials could be markedly altered during SARS-CoV-2 acute respiratory failure, which should encourage to perform therapeutic drug monitoring.